$a$, $b$ and $c$ are three literals. They have a mathematical relation through common logarithm and ratio. The relation between them are given here.

$\dfrac{\log a}{b-c}$ $\,=\,$ $\dfrac{\log b}{c-a}$ $\,=\,$ $\dfrac{\log c}{a-b}$

The value of the product $a$, $b$ and $c$ is required to find by using this data.

01

$abc$ is a product of three literals $a$, $b$ and $c$. Fortunately, there is a logarithmic identity to express the product of the terms as sum of their logs. So, use the product rule of logarithms and express log of product of $a$, $b$ and $c$ as sum of their logs.

$\log abc$ $\,=\,$ $\log a + \log b + \log c$

02

According to the given data of this problem. every logarithmic term can be transformed into another logarithmic term. So, let us transform the first two terms in terms of the $\log c$.

$\dfrac{\log a}{b-c} = \dfrac{\log c}{a-b}$

$\implies \log a = (b-c) \times \dfrac{\log c}{a-b}$

$\therefore \,\,\,\,\,\, \log a = \dfrac{b-c}{a-b} \times \log c$

In the same way,

$\dfrac{\log b}{c-a} = \dfrac{\log c}{a-b}$

$\implies \log b = (c-a) \times \dfrac{\log c}{a-b}$

$\therefore \,\,\,\,\,\, \log b = \dfrac{c-a}{a-b} \times \log c$

Now, replace the terms $\log a$ and $\log b$ in the logarithmic equation.

$\implies$ $\log abc$ $\,=\,$ $\dfrac{b-c}{a-b} \times \log c$ $+$ $\dfrac{c-a}{a-b} \times \log c$ $+$ $\log c$

$\log c$ is a common factor in the three terms of the equation. So, take it common from them.

$\implies$ $\log abc$ $\,=\,$ $\log c \times \Bigg[\dfrac{b-c}{a-b} + \dfrac{c-a}{a-b} + 1\Bigg]$

$\implies$ $\log abc$ $\,=\,$ $\log c \times \Bigg[\dfrac{b-c + c-a + a-b}{a-b}\Bigg]$

$\implies$ $\log abc$ $\,=\,$ $\require{cancel} \log c \times \Bigg[\dfrac{\cancel{b} -\cancel{c} + \cancel{c} -\cancel{a} +\cancel{a} -\cancel{b}}{a-b}\Bigg]$

$\implies$ $\log abc$ $\,=\,$ $\log c \times \Bigg[\dfrac{0}{a-b}\Bigg]$

$\implies$ $\log abc \,=\, \log c \times 0$

$\implies$ $\log abc \,=\, 0$

03

In order to obtain the value of $abc$, write the equation $\log abc = 0$ in exponential form as per the mathematical relation between logarithms and exponents.

$\implies$ $abc \,=\, 10^0$

Use power rule of zero exponent to evaluate $10$ raised to the power of zero.

$\therefore \,\,\,\,\,\,$ $abc \,=\, 1$

Therefore, the product of the literals $a$, $b$ and $c$ is $1$ and it is the required solution for this logarithmic problem.

Latest Math Topics

Latest Math Problems

A best free mathematics education website for students, teachers and researchers.

Learn each topic of the mathematics easily with understandable proofs and visual animation graphics.

Learn how to solve the maths problems in different methods with understandable steps.

Copyright © 2012 - 2022 Math Doubts, All Rights Reserved